How do product market regulations affect workers? Evidence from the network industries - Denk, Oliver (Paris, 2016)
"Knowing who gains and loses from regulatory reform is important for understanding the political economy of reform. Using micro-level data from 26 countries, this paper studies how regulatory reform of network industries, a policy priority in many advanced economies, influences the labour market situation of workers in network industries. Estimates are identified from changes in a worker’s pay, industry-level employment flows and regulation over time. The main finding is that the regulation of network industries provides workers in this industry with a wage premium and higher employment stability relative to similar workers in other industries. Regulatory reform therefore tends to align labour income and employment stability in the reformed industry with those in other industries. Workers in the reformed industry lose out compared with others, because they no longer benefit from “excess” pay and employment stability."